Improved Beerkan run methodology to assess water impact effects on infiltration and hydraulic properties of a loam soil under conventional‐ and no‐tillage. Issue 2 (15th March 2021) - Castellini, Mirko; Stellacci, Anna Maria; Di Prima, Simone; Iovino, Massimo; Bagarello, Vincenzo
Abstract: Beerkan infiltration experiments with three water pouring heights (low, L = 3 cm; intermediate, M = 100 cm; high, H = 200 cm) were performed on both a no‐tilled (NT) and a conventionally tilled (CT) bare loam soil to determine the surface soil hydraulic properties by the BEST‐steady algorithm. Saturated soil hydraulic conductivity, K s, significantly and monotonically decreased from the L to the H runs (from 236 to 37 mm h ‒1 ) and lower K s values were detected under CT (163–23 mm h ‒1 ) than NT (346–51 mm h ‒1 ) for each water pouring height. For both soil management practices, the gravitational potential energy, E p, of the water used for the infiltration runs, explained most of the variance in the mean K s values. According to the fitted relationships, an increase of E p from 50 to 3, 327 J m ‒2 determined a K s decrease by a factor of 9.5 in the CT soil and 6.3 in the NT soil. The CT soil was 2.1 and 3.3 times less conductive than the NT soil with the lowest and the highest energy, respectively. The water retention scale parameter, hg, only varied between non‐perturbing (L) and perturbing (M, H) runs because | hg | increased from 55 to 93–100 mm. Therefore, water impact can greatly influence hydrodynamic properties of the upper soil layer regardless of the management practice. The tested infiltration methodology looks promising to mimic effects of relatively high energy rainfall events and to determine the hydraulic properties of the exposed soil layer under different management practices. Core Ideas: The effect of the water impact on hydraulic properties of the altered soil was studied. Beerkan experiments with three water pouring heights (0.03–1–2 m) were performed. A no‐tilled (NT) and a conventionally tilled (CT) bare loam soil were investigated. K s significantly and monotonically decreased in the passage from low to high runs. The lowest K s can be viewed as a hydrological indicator showing favorable condition to runoff.